Effects of low-volume, high-intensity interval training on maximal oxygen consumption, body fat percentage and health-related quality of life in women with overweight: A randomized controlled trial - Víctor H. Arboleda-Serna; Fredy A. Patiño-Villada; Deiber A. Pinzón-Castro; Elkin F. Arango-Vélez (Elsevier, 2022)
Background/Objectives: Several investigations suggest that high-intensity interval training (HIIT) provokes larger changes in VO2max compared to moderate-intensity continuous training (MICT); other studies associate HIIT with significant decreases in total, abdominal and visceral fat mass. However, some meta-analyses express that the enhancements with HIIT on VO2max are slightly higher concerning MICT. These studies had low-to-moderate methodological quality, and the exercise protocols were completed mostly on treadmills or cycle ergometers. Thus, the objective of this study was to compare the effect of a low-volume HIIT versus a MICT program on VO2max, body fat percentage (BFP), and health-related quality of life (HRQoL) in overweight women. It followed a research protocol with high methodological rigor and good reporting quality. Methods: After two physical adaptation weeks (run-in period), thirty-five volunteers were randomized to HIIT (n = 16) or MICT (n = 19). Both groups performed 24 sessions on a grass sports field (walking, jogging or running). The HIIT group completed 15 bouts of 30 s [90-95%, maximal heart rate (HRmax)], while the MICT group completed 30 min of continuous exercise (65-75% HRmax). Results: The difference between HIIT and MICT post-intervention on VO2max was not statistically significant (0.8 ml/kg/min. CI 95%, −1.0 to 2.7, p = 0.37). Similarly, no statistically significant differences were found between groups for BFP and HRQoL. Conclusions: Low-volume HIIT program has no quantitative advantage compared with that resulting from MICT, in VO2max, BFP, and HRQoL. ClinicalTrials.gov Identifier: NCT03300895.